Strategi Pemasaran Online Pada Hidea Coffee Shop - Agustina Fitrianingrum; Aprila Utari Prasesa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
The coffee industry has rapidly grown in many cities of Indonesia, including Batam. Currently, Starbuck is the big player for the international brand coffee cafe. The tight competition encourages local coffee cafes to design a digital marketing platform form of digital marketing. Social media as promotional media nowadays has become a current trend to introduce a product and become one of the solutions during a pandemic. Instagram ads are one of the most widely used promotional media to advertise products. The implementation of this program increases the efficiency of using Instagram ads at Hidea Coffee Shop. The evaluation has developed using the aspect of Insight Engagement Customer coverage. This tool helps Hidea Coffee Shop to reach the target market.